Oncosis-inducing cyclometalated iridium(iii) complexes - Guan, Ruilin (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Oncosis is a non-apoptotic form of programmed cell death (PCD), which differs from apoptosis in both morphological changes and inner pathways, and might hold the key to defeating a major obstacle in cancer therapy – drug-resistance, which is often a result of the intrinsic apoptosis resistance of tumours. However, despite the fact that the term “oncosis” was coined and used much earlier than apoptosis, little effort has been made to discover new drugs which can initiate this form of cell death, in comparison to drugs inducing apoptosis or any other type of PCD. So herein, we present the synthesis of a series of mitochondria-targeting cyclometalated Ir(iii) complexes, which activated the oncosis-specific protein porimin and calpain in cisplatin-resistant cell line A549R, and determined their cytotoxicity against a wide range of drug-resistant cancer types. To the best of our knowledge, these complexes are the very first metallo-components to induce oncosis in drug-resistant cancer cells.